Pengaruh Terapi Berbasis Aplikasi Seluler Dalam Menurunkan Nyeri Pada Pasien Osteoartritis Lutut : Systematic Review - Muthia, Ellen; Masfuri, Masfuri; Arista, Liya; Maria, Riri (Jurnal Ners, 2025)
Knee osteoarthritis is a degenerative condition that often causes significant pain and thus affects the patient's quality of life. Mobile application-based therapy is a non pharmacological physical rehabilitation method that has emerged as an innovative approach in reducing pain and providing self-management benefits to increase adherence with therapy programs. This systematic review aims to determine the effect of mobile application-based therapy in reducing pain in knee osteoarthritis patients. A literature search was conducted using the EBSCO, Pubmed, ScienceDirect, and Scopus databases from 2020 to 2024 to identify randomized controlled trials (RCT) articles on mobile application-based therapy in knee osteoarthritis patients in the context of knee osteoarthritis pain therapy. Data regarding pain reduction, patient adherence, and functional outcomes were extracted and analyzed. Results obtained from 7 RCT articles showed that mobile application-based therapy significantly reduced pain in knee osteoarthritis patients compared with the control group. Apps that provide exercise programs, education, and self-monitoring have shown that increased patient adherence to therapy has been found to be positively associated with better pain outcomes. The conclusion is that mobile application-based therapy provides benefits in pain management in knee osteoarthritis patients. Further research is needed to explore factors that influence the success of therapy.